Suitability of Converting Debt Into Shares As A Means of Homologizing Company Bankruptcy - Sari, Novita; Rifai, Anis; Machmud, Aris (IHSA Institute, 2024)
The present paper examines the efficacy of debt conversion into shares as a means of corporate bankruptcy homologation, with particular emphasis on Waskita's vendor debt case study. In this case, one possible way to repair business finances and pay off debts to creditors—particularly vendors—is to convert debt into shares. Postponement of debt payments refers to the suspension of debt payments for a predetermined amount of time as stipulated by law. During this time, debtors and creditors can talk about debt settlement options through rulings made by commercial courts. This entails creating a repayment schedule that can call for restructuring the debt in addition to paying back the entire amount owed. Because it stresses the use of secondary data to explain the homologation process and the effects of converting debt into shares at PT Waskita Beton Precast Tbk (WSBP), this research employs a normative legal approach. The findings of this study indicate that submitting a Peace Plan by the PKPU Debtor, PT Waskita Beton Precast, Tbk (In PKPU), is appropriate. The actions conducted by the PKPU Debtor are compliant with the terms of Article 281 paragraph (1) of Law Number 37 of 2004 about Bankruptcy and Postponement of Debt Payment Obligations, given that the voting results regarding the settlement plan have been completed. Recalling that on June 17, 2022, PT Waskita Beton Precast, Tbk (In PKPU) was a party to the Peace Agreement pertaining to the Peace Plan, and that on that same day, PKPU Debtors and Creditors were present and took part in the voting on the Peace Plan, which was approved